STUDENTS THROUGH INTEGRATED LESSONS IN PRIMARY CLASSES EXPANDING ONE'S WORLD VIEW (Western European Journal of Linguistics and Education, 2024)
The article describes the importance of integrating primary school classes and expanding the worldview of primary school students through integrated classes